DESAIN DAN IMPLEMENTASI INSTRUMEN DIGITAL PENGUKUR KECEPATAN, JARAK DAN PEMBAKARAN KALORI PADA SEPEDA GUNUNG BERBASIS MIKROKONTROL ATMEGA32 - Lantana Dioren Rumpa (Journal Dynamic Saint, 2016)
Bicycle is one of the most popular transportation and in Indonesia there are still many people used it. Static bike or stationary bicycle is one of many kind of bicycle and people used it in indoor room. Static bike has an electronic panel that could help people who used it to know how far the distance, what abaout their speed and how many calories they have burned. Many people said that static bike is more fun and more interesting than outdoor bicycle especially from mountain bike because the static bike has the electronic panel. The electronic panel from static bike will be used on mountain bike so it can be more interresting as static bike. Microcontroller will used as minicomputer to processing all data from magnetic sensor that show the rotation of bike’s tires and then the microcontroller will show the result on seven segment display about the distances, the speed, and the calories burned.